A novel approach for improving the yield of Bacillus subtilis transglutaminase in heterologous strains. (1st August 2014) - Liu, Yihan; Lin, Song; Zhang, Xiqing; Liu, Xiaoguang; Wang, Jianling; Lu, Fuping
Abstract: The transglutaminase (BTG) from Bacillus subtilis is considered to be a new type of transglutaminase for the food industry. Given that the BTG gene only encodes a mature peptide, the expression of BTG in heterologous microbial hosts could affect their normal growth due to BTG's typical transglutaminase activity which can catalyze cross-linking of proteins in the cells. Therefore, we developed a novel approach to suppress BTG activity and reduce the toxicity on microbial hosts, thus improving BTG yield. Genes encoding the respective regions of transglutaminase propeptide from seven species of Streptomyces were fused to the N-terminal of the BTG gene to produce fusion proteins. We found that all the fused propeptides could suppress BTG activity. Importantly, BTG activity could be completely restored after the removal of the propeptides by proteolytic cleavage. Of the seven propeptides tested, the propeptide proD from Streptomyces caniferus had the strongest suppressive effect on BTG activity (70 % of the activity suppressed). Moreover, fusion protein proD-BTG (containing proD) also exhibited the highest yield which was more than twofold of the expression level of BTG in an active form in Escherichia coli . Secretion expression of BTG and proD-BTG in Corynebacterium glutamicum further showed that our novel approach was suitable for the efficient BTG expression, thus providing a valuable platform for further optimization of large-scale BTG production.